Analysis Of The Implementation Of Financial Accounting Standards For Entities Without Public Accountability (SAK ETAP) In The Preparation Of Financial Reports At PT. BPR Tahap Ganda Prabumulih - Tenny, Tenny Dwita Amalia; Sartika, Dewi (SEAN Institute, 2024)
Accounting aims to produce financial reports that provide accountability to internal and external parties of the company. Financial reports contain information concerning the financial position and aim to assist entities in making decisions. In making financial reports, there are also standards that must be adhered to. These standards are needed because of the many users of financial reports. If there are no standards, companies can simply present their financial reports according to their own wishes. In Indonesia, there are four types of accounting standards that are used as a reference for companies to make financial reports, one of which is the Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP). SAK ETAP is specifically designed for entities that do not have public accountability such as BPR. The objective to be achieved in this study is to determine whether the financial reports of BPR Tahap Ganda Prabumulih are in accordance with the Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP). This type of research is qualitative research. Data obtained by conducting interviews, observations, and documentation. The steps taken by the researcher are: 1) conducting direct interviews with employees to obtain research data regarding the financial reports of BPR Tahap Ganda. 2) Analyze the financial statements in 2022 of PT. BPR Tahap Ganda according to SAK ETAP to see the suitability of the presentation of financial statements based on SAK ETAP. 3) Draw conclusions about SAK ETAP in the presentation of financial statements of PT. BPR Tahap Ganda. The results of the analysis in this study indicate that the financial statements of BPR Tahap Ganda are in accordance with SAK ETAP. This can be proven that BPR Tahap Ganda has presented complete financial statements in accordance with SAK ETAP, namely the Balance Sheet, Income Statement, Cash Flow Statement, Statement of Changes in Equity, and Notes to the Financial Statements. Although there are some differences in account names in the income statement items and notes to the financial statements.